Cytotoxicity of acrylic resin-based materials used to fabricate interim crowns - Souza, Isabela R. [UNESP]; Pansani, Taisa N. [UNESP]; Basso, Fernanda G.; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos A. [UNESP] (Elsevier, 2020)
Statement of problem: If the components in the acrylic resins used to fabricate interim crows are cytotoxic, they can interfere with the integrity of the adjacent periodontal tissue and the dentin-pulp complex. Purpose: The purpose of this in vitro study was to assess the cytotoxicity of resin-based materials used to prepare interim crowns. Material and methods: The following materials were used in this study: CAR, conventional acrylic resin powder and liquid; BR, bis-acrylic resin; and PAR, pressed acrylic resin of the CAD-CAM type. Glass disks were used as the control (Co). Oral epithelial cells (NOK) were seeded on glass disks and standardized disks prepared with the resins under study. After incubation for 24 hours, the cells were analyzed for viability (Alamar Blue and Live or Dead), adhesion, and morphology (SEM and fluorescence), as well as epidermal growth factor synthesis (EGF-ELISA). The surface roughness (Ra) of test specimens was evaluated under a confocal microscope. The data were submitted to ANOVA and the Tukey HSD statistical tests (α=.05). Results: The highest Ra value was observed in BR in comparison with CAR, PAR, and Co (P<.05). The highest viability, adhesion, and EGF synthesis values were determined for the cells in contact with PAR (P<.001). Conclusions: The computer-aided design and computer-aided manufacturing (CAD-CAM)-type resin favored adhesion, metabolism, and epithelial cell proliferation, and it was therefore considered cytocompatible.